CO2 storage in the Antarctica Sub-Continental Lithospheric Mantle as revealed by intra- and inter-granular fluids - Federico Casetta (Department of Lithospheric Research, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Andrea L. Rizzo (Sezione di Palermo, Istituto Nazionale di Geofisica e Vulcanologia, Italy); Barbara Faccini (Department of Physics and Earth Sciences, University of Ferrara); Theodoros Ntaflos (Department of Lithospheric Research, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Rainer Abart (Department of Lithospheric Research, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Gabriele Lanzafame (Department of Biological, Geological and Environmental Sciences, University of Catania); Luca Faccincani (Department of Physics and Earth Sciences, University of Ferrara); Lucia Mancini (Elettra-Sincrotrone Trieste S.C.p.A); Pier Paolo Giacomoni (Department of Physics and Earth Sciences, University of Ferrara); Massimo Coltorti (Sezione di Palermo, Istituto Nazionale di Geofisica e Vulcanologia, Italy) (Lithos, 2022)
The abstract is available here: https://uscholar.univie.ac.at/o:1628571 The abstract is available here: https://uscholar.univie.ac.at/o:1628571